1985
DOI: 10.1136/hrt.53.4.374
|View full text |Cite
|
Sign up to set email alerts
|

Mitral valve prolapse in hyperthyroidism of two different origins.

Abstract: The prevalence of mitral valve prolapse was investigated in 126 patients with hyperthyroidism due to Graves' disease or toxic nodular goitre and that of hyperthyroidism in 64 patients with mitral valve prolapse. One hundred and eleven asymptomatic healthy subjects comprised a control group. The patients with hyperthyroidism were divided into those with Graves' disease and those with toxic nodular goitre. Of the group as whole, 12 (9.5%) patients had mitral valve prolapse compared with six (5.4%) in the control… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
13
0
2

Year Published

1987
1987
2012
2012

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(17 citation statements)
references
References 24 publications
2
13
0
2
Order By: Relevance
“…After the description by Channick et al [1] of the increased prevalence of mitral valve prolapse in Graves' disease, we rein vestigated the problem and confirmed their findings in a much larger group [2]. In searching for an explanation of this associa tion, a common autoimmune etiology was suggested as only Graves' disease was associ ated with the cardiac abnormality while thy rotoxicosis of nonimmune origin showed an incidence similar to that of the normal pop ulation.…”
supporting
confidence: 48%
“…After the description by Channick et al [1] of the increased prevalence of mitral valve prolapse in Graves' disease, we rein vestigated the problem and confirmed their findings in a much larger group [2]. In searching for an explanation of this associa tion, a common autoimmune etiology was suggested as only Graves' disease was associ ated with the cardiac abnormality while thy rotoxicosis of nonimmune origin showed an incidence similar to that of the normal pop ulation.…”
supporting
confidence: 48%
“…An increased prevalence of MVP has been reported in Graves' disease and chronic lymphocytic thyroiditis, but the pathophysiological mechanisms linking MVP and autoimmune thyroid disease are still not understood. [7][8][9][10][11] In recent years, a germline mutation of the TSHR gene (P639S) was reported to be associated with thyrotoxicosis and MVPS in a Chinese family.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have reported that the prevalence of MVP is significantly elevated in Graves' disease and chronic lymphocytic thyroiditis, but not in toxic multinodular goiter. [7][8][9][10] The pathophysiological mechanisms linking MVP and autoimmune thyroid disease are still not understood. It has been suggested that human leukocyte antigen genes may explain the linkage between Graves' disease and MVP.…”
mentioning
confidence: 99%
“…According to our data, the prevalence of PH was 29% in ST, and 39.6% in overt thyrotoxicosis. The prevalence of mitral valve prolapse is 18-41% in thyrotoxicosis compared to 6-20% in general population (Brauman et al, 1985, Kahaly, 1986, Evangelopoulou et al, 1999.…”
Section: Arrhythmiasmentioning
confidence: 99%
“…First mechanism includes induction of glycosaminoglycan synthesis in endocardium (similar to one in retrobulbar space in ophthalmopathy) leading to the valve cusp thickening (Kahaly, 1987). The second one implies the reduced tone of papillary muscles and their consequent overstretching resulting in prolapse of mitral valve cusps in left atrium during ventricular systole (Brauman et al, 1985). Pulmonary hypertension develops due to Kitaev reflex -spasm of pulmonary arterioles leading to the increase of pulmonary resistance (Okura & Takatsu, 1994).…”
Section: Effects Of Thyroid Hormones Pathogenesis Of Influence Of Thymentioning
confidence: 99%